Influence of Sex on Outcomes After Thoracic Endovascular Repair for Type B Aortic Dissection. (July 2021) - Luo, Songyuan; Zhu, Yi; Xie, Enmin; Ding, Huanyu; Yang, Fan; Chen, Lyufan; Liu, Jitao; Liu, Yuan; Xue, Ling; Fan, Ruixin; Luo, JianFang; Chen, Jiyan
We aimed to investigate whether sex differences influence the clinical outcomes of patients who undergo thoracic endovascular aortic repair (TEVAR) for type B aortic dissection (TBAD). We retrospectively analyzed a prospectively maintained single-center cohort of patients with TBAD who underwent TEVAR between January 2010 and June 2017. We evaluated the in-hospital and long-term mortality and composite end point. Of the 913 patients, 793 (86.8%) were male and 120 (13.1%) were female. Compared to male patients, the female patients were older, more likely to have diabetes mellitus, but less likely to smoke or have hypertension. The proximal landing zone in 0 and 1 was higher in male patients ( P = .023), who were more likely to require an aortic arch bypass. Endoleak, delirium, and ICU stay after stent-graft implantation were also more frequent in men. Sex factor was not associated with in-hospital or long-term mortality or the composite end point in the multivariable regression analyses and Cox regression model. The mean estimated survival time was similar between males and females (2462.9 ± 141.2 vs 2804.1 ± 117.4 days, P = .167) in the propensity score–matched cohort. Despite distinct characteristics between sex, there was no sex-related difference in long-term clinical outcomes after TEVAR for TBAD.